Economic complexity and environmental pollution: evidence from the former socialist transition countries - Florian Bucher; Lucas Scheu; Benedikt Schröpf (Empirica, 2023)
AbstractThis study examines the link between economic complexity and environmental pollution by exploiting a massive and unprecedented decline of CO2 emissions and complexity in the former socialist transition countries after the fall of the iron curtain. We refer to the extended theories of the Environmental Kuznets Curve (EKC), stating that environmental pollution follows an inverted u-shaped course with respect to economic complexity. Using comprehensive data of 27 countries for the period 1995–2017, our results show that the EKC can be found for countries whose complexity rose over time. Additionally, since the results for production-based and consumption-based CO2 emissions are similar, we can discard emissions offshoring as a major explaining factor. Consequently, our findings suggest that more complex products have influenced the u-shaped course of the EKC. However, as the turning point is associated with high levels of pollution, our estimates imply that complexity may even exacerbate environmental issues in the short and middle run in less developed countries.
Keywords: O44; P2; 330; Economic complexity; Environmental Kuznets Curve; Former socialist states